FTO variant associated with malformation syndrome. Issue 4 (24th December 2015) - Rohena, Luis; Lawson, Michelle; Guzman, Edwin; Ganapathi, Mythily; Cho, Megan T.; Haverfield, Eden; Anyane‐Yeboa, Kwame
Abstract : Common FTO variants are associated with obesity. However, it has recently been shown that homozygous FTO c.947G>A variant, which predicts p.R316Q, and c.956C>T, which predicts p.S319F, are associated with a malformation syndrome inherited in an autosomal recessive pattern. We present a similar homozygous FTO c.965G>A variant that predicts p.R322Q, associated with a lethal malformation syndrome in a consanguineous Yemeni family. Functional studies showed that the p.R316Q, p.S219F, and p.R322Q variants render the FTO protein inactive. We further expand on the phenotype of homozygous FTO loss‐of‐function mutations to include eye abnormalities, gingival overgrowth, craniosynostosis, and cutaneous photosensitivity. © 2015 Wiley Periodicals, Inc.